DIVISION OF SPOUSES' CORPORATE RIGHTS:REGULATORY FRAMEWORK AND JUDICIAL PRACTICE - РАДЧЕНКО, Лілія (Київський національний університет імені Тараса Шевченка, 2026)
B a c k g r o u n d . The article examines the peculiarities of the distribution of corporate rights of spouses in legislation and national judicial practice. Trends in the consideration and resolution by courts of disputes concerning the division of joint property of spouses that is the subject of corporate relations are identified. Conclusions and proposals for improving the national system of legal regulation of family relations are formulated. M e t h o d s . In the process of identifying and analysing the peculiarities of the division of corporate rights of spouses and their consequences in legislation, legal doctrine and judicial practice, general philosophical and special legal methods of researching social patterns, legal phenomena and legal categories were applied. R e s u l t s . As a result of considering the peculiarities of the division of corporate rights of spouses through the prism of legislative regulation and judicial practice, the absence of special normative provisions both at the level of the Family Code of Ukraine and within the framework of corporate legislation regarding the determination of the legal regime of corporate property formed at the expense of the joint property of spouses in particular, as a contribution to the authorised capital of a legal entity, as such, the right to which is enjoyed by both spouses (even if the other spouse is not a participant or founder of the legal entity), unless otherwise specified in the agreement between the spouses. The lack of necessary legal regulation has led to the development of various approaches in judicial practice regarding the ownership of property by corporations and the joint ownership of spouses. C o n c l u s i o n s . Legal relations regarding the division of corporate rights of spouses require proper legal regulation that would take into account the main developments in judicial practice, in particular in terms of establishing that the objects of joint shared ownership of spouses are property transferred by one of them as a contribution (investment) of a participant to the authorised capital of a legal entity. In the event of divorce, the participant's contribution to the authorised capital, which is the object of joint property of spouses, is subject to division between the spouses, taking into account its value on the date of division, unless otherwise specified in the agreement between the spouses. The consolidation of this provision at the regulatory level will contribute to the certainty of the rights and obligations of spouses and reduce the number of court disputes in this category of cases.

В с т у п . Досліджено особливості розподілу корпоративних прав подружжя у законодавстві України та в національній судовій практиці; визначено тенденції розгляду та вирішення судами спорів щодо поділу спільного майна подружжя, що є об'єктом корпоративних відносин; сформульовано висновки та пропозиції з удосконалення національної системи правового регулювання сімейних відносин. М е т о д и . У процесі визначення особливостей поділу корпоративних прав подружжя у законодавстві, правовій доктрині та судовій практиці було застосовано загальнофілософські та спеціально-юридичні методи дослідження соціальних закономірностей, правових явищ і юридичних категорій. Р е з у л ь т а т и . У результаті розгляду правових засад поділу корпоративних прав подружжя крізь призму законодавчого регулювання та судової практики визначено відсутність спеціальних нормативних положень як на рівні СК України, так і в межах корпоративного законодавства щодо визначення правового режиму корпоративного майна, сформованого за рахунок спільного майна подружжя, зокрема як внеску до статутного капіталу юридичної особи. Відсутність необхідного рівня правового регулювання має наслідком формування різних підходів судової практики до того, яке майно належить корпорації, а яке є спільною сумісною власністю подружжя. В и с н о в к и . Правовідносини щодо поділу корпоративних прав подружжя потребують належної правової регламентації, яка б ураховувала основні напрацювання судової практики, зокрема в частині фіксації положення про те, що об'єктом спільної сумісної власності подружжя є майно, передане одним із них як внесок (вклад) учасника до статутного капіталу юридичної особи. При розлученні внесок учасника до статутного капіталу, що є об'єктом спільної сумісної власності подружжя, підлягає поділу між подружжям з урахуванням його вартості на дату поділу, якщо інше не визначено договором між подружжям. Закріплення зазначеного положення на нормативному рівні сприятиме визначеності прав та обов'язків подружжя і зменшенню кількості судових спорів із цієї категорії справ.
РОЗПОДІЛ КОРПОРАТИВНИХ ПРАВ ПОДРУЖЖЯ:НОРМАТИВНЕ РЕГУЛЮВАННЯ ТА СУДОВА ПРАКТИКА
Keywords: spouses; corporate rights; participant's contribution; dividends; divorce.; подружжя; корпоративні права; внесок учасника; дивіденди; розлучення.